Nursing Care Services of Secondary Hospitals (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Nurses are critical to delivering high-quality, efficient care contributory to the healthcare experiences of patients. In fact, this could have a major impact on their satisfaction as receivers of various hospital services. Patients, through their experiences, offer insights into hospital quality, which would be unseen from other perspectives, as they are often the only people to view the quality of care holistically (Rathert, Wyrwich & Boren, 2011). This led to the conduct of this study to determine the quality of nursing care services in the secondary hospitals in the Ilocos Sur Province. The descriptive survey research design was made to ascertain the level of satisfaction of patients and watchers on the nursing care given to them as well as the strengths and weaknesses of these services in the identified areas using a survey questionnaire. The participants of the study included 90 nurses and 90 patients, and watchers. The patients and nurses were purposedly selected based on the established inclusion criteria of the study. The weighted mean and independent samples t-test were utilized for the statistical treatment of the gathered data. The results revealed that the respondents were satisfied highly with these nursing services: admission and discharge, patient comfort and safety, and on medication and treatment, while the spiritual care came out as the weakness. Furthermore, the nurse respondents and the patient/watcher-respondents did not significantly differ in their level of satisfaction with nursing services. The findings of the study assure the public that nursing care in secondary hospitals in the Province of Ilocos Sur adheres to patient care and service satisfaction. It also offers opportunities to sustain the commendable status of the services and to continue exploring various means to achieve total satisfaction of nursing services, particularly in spiritual nursing care.
Keywords: nursing care services, secondary hospital, patient satisfaction